Automation when skills are bundled - Sofia Hernnäs (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
Automation affects workers because it affects the return to their skills when performing different tasks. I propose a general equilibrium model of occupational choice and technological change which takes two important labor market features into account: (i) automation happens to tasks and (ii) workers have bundled skills. Equilibrium skill returns vary across tasks, and the impact of automation on skill returns is task-specific. I find that, to a first-order approximation, skill returns depend only on the relative skill allocation in each task. In equilibrium, automation reduces employment in the task subjected to automation so long as tasks are gross complements. This reduction in employment increases both tasks' intensity in the skill used intensively in the automated task. This increased intensity is coupled with a universal decline in the return to the skill used intensively in the automated task. Conversely, the return to the other skill increases in both tasks.
Keywords: 330; Automatisierung; Technischer Fortschritt; Qualifikation; Anforderungsprofil; Berufswahl; Allgemeines Gleichgewicht; Komparative Statik